Comodulation Masking Release induced by controlled electrical stimulation of auditory nerve fibers - Zirn, Stefan; Hempel, John-Martin; Schuster, Maria; Hemmert, Werner (Hearing research, 2013)
Normal-hearing listeners can perceptually segregate concurrent sound sources, but listeners with significant hearing loss or who wear a Cochlear Implant (CI) lag behind in this ability. Perceptual grouping mechanisms are essential to segregate concurrent sound sources and affect Comodulation Masking Release (CMR). Thus, CMR measurements in CI users could shed light on segregation cues needed for forming and grouping of auditory objects. CMR illustrates the fact that detection of a target sound embedded in a fluctuating masker is improved by the addition of masker energy remote from the target frequency, provided the envelope fluctuations across masker components are coherent. We modified such a CMR experiment to electrically-induced hearing using direct stimulation and measured the effect in 21 CI users. Cluster analysis of our data revealed two groups: one showed no or only small CMR of 0.1 dB ± 2.7 (N = 14) and a second group achieved a CMR of 10.7 dB ± 3.2 (N = 7), a value that is close to the enhancement observed in a comparable acoustic experiment in normal-hearing listeners (12.9 dB ± 2.6, N = 6). Interestingly, we observed that CMR in CI users may relate to hearing etiology and duration of hearing loss pre-implantation. Our study demonstrates for the first time that a substantial minority of cochlear-implant listeners (about a third) can show significant CMR. This outcome motivates the development of physiologically inspired multi-band gain control and/or different coding strategies for these groups in order to better preserve coherent modulation and thus to take advantage of the individual remaining capabilities to analyze spectro-temporal patterns. ► Comodulation masking release measurements in cochlear implant users. ► Masker components and target signal addressed to intra-cochlear electrodes. ► Realization: controlled channel specific stimulation (Nucleus Implant Communicator). ► Results: 66% of test subjects showed no CMR, 33% significant CMR. ► Etiology and duration of hearing loss pre-implantation were indicators for electrically induced CMR.